2006
DOI: 10.5326/0420350
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Cats With Oral Tumors Treated With Mandibulectomy: 42 Cases

Abstract: Medical records of 42 cats treated with mandibulectomy for oral neoplasia at eight institutions were reviewed to determine morbidity, progression-free interval, and survival time. Progression-free and survival rates at 1 and 2 years were 56% and 49%, and 60% and 57%, respectively. Cats with squamous cell carcinoma had significantly shorter survival than cats with fibrosarcoma or osteosarcoma. Seventy-two percent of cats were dysphagic or inappetent immediately postoperatively, and 12% never regained the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(109 citation statements)
references
References 6 publications
3
99
3
4
Order By: Relevance
“…Given the advanced stage at diagnosis in most feline patients, local surgical excision is not considered a curative treatment. The mandible is considered the anatomic region most amenable to surgical resection and when deemed feasible in select cases, mandibulectomy results in median survival times of 5–12 months [2630]. Given the importance of both functional outcome and primary tumor control, surgical decisions must account for both morbidity and the likelihood of achieving complete excision.…”
Section: Head and Neck Squamous Cell Carcinoma (Hnscc) Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the advanced stage at diagnosis in most feline patients, local surgical excision is not considered a curative treatment. The mandible is considered the anatomic region most amenable to surgical resection and when deemed feasible in select cases, mandibulectomy results in median survival times of 5–12 months [2630]. Given the importance of both functional outcome and primary tumor control, surgical decisions must account for both morbidity and the likelihood of achieving complete excision.…”
Section: Head and Neck Squamous Cell Carcinoma (Hnscc) Modelingmentioning
confidence: 99%
“…In one study, acute and long-term postoperative morbidity were observed in 98% and 76% of the cats, respectively, with 12% of cats never regaining functional ability to eat. Despite curative-intent surgical approaches, 48% of tumor specimens had evidence of residual disease histologically [30]. In one small study, the combination of mandibulectomy and radiation therapy (RT) resulted in a median survival of 14 months, suggesting that for select cases, a better long-term prognosis may be feasible [31].…”
Section: Head and Neck Squamous Cell Carcinoma (Hnscc) Modelingmentioning
confidence: 99%
“…10 Treatment is often hampered by the locally aggressive nature of these tumors 10 and the high morbidity that may be seen with treatment. 6 Feline oral SCC shares many similarities with human head and neck cancer (HNSCC), which is also highly invasive and carries a poor prognosis. 11 Patients that present with locoregional advanced disease have a median survival of 19.1 months with chemoradiation treatments.…”
Section: Introductionmentioning
confidence: 99%
“…4 SCC accounts for up to three quarters of oral tumors reported in cats. 5 Several treatment options are available including surgery, 6 radiotherapy, 7 chemotherapy 8 or a combination of these, 9 but overall survival remains poor. 10 Treatment is often hampered by the locally aggressive nature of these tumors 10 and the high morbidity that may be seen with treatment.…”
Section: Introductionmentioning
confidence: 99%
“…87 Bilateral resection caudal to this level or unilateral mandibular body resection results in loss of the mandibular symphysis, "floating" of the remaining mandibular sections, and progressively greater problems with tongue retention, eating, and grooming. 87 Bilateral resection caudal to this level or unilateral mandibular body resection results in loss of the mandibular symphysis, "floating" of the remaining mandibular sections, and progressively greater problems with tongue retention, eating, and grooming.…”
Section: Staging Oral Examination and Biopsymentioning
confidence: 99%